Understanding User Adoption Of Indonesia’s Boarding House Rental App Through The Extended Technology Acceptance Model - Generosa Lukhayu Pritalia; Darren, Oktavianus; Wibisono, Priadi (Program Studi Teknik Informatika Universitas Pamulang, 2025)
The Mamikos mobile application has become a popular platform for housing seekers in Indonesia. It has garnered a rating of 4.1 on the Play Store and 4.7 on the App Store. However, the factors influencing user acceptance and usage of the Mamikos mobile application remain unclear. This study aims to examine these factors using the extended Technology Acceptance Model (TAM) approach. Data was collected using purposive sampling. The Lemeshow formula was employed to determine the appropriate sample size, resulting in 168 respondents. Data analysis was conducted using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. The findings indicate that social trust has a significant positive influence on both perceived usefulness and perceived ease of use. Perceived ease of use, in turn, has a significant positive influence on both perceived usefulness and attitude towards use. Subjective norms exert a significant positive influence on attitude towards use. Perceived usefulness significantly impacts attitude towards use, which in turn significantly affects intention to use. Intention to use has a significant positive influence on actual system usage. However, subjective norms do not significantly influence perceived usefulness.